How Team Management Influences Organizational Welfare: Islamic Perception (Salam International Academic Journal, 2020)
Purpose  Study on hand undertaken here discusses the effect of the Islamic concept of team management and its relations with social welfare considering ten different private sector organizations in Kabul, Afghanistan.Population / Sampling:  For current study 20 private organizations were selected among which 250 employees participated to provide answer to the adopted questionnaire, there is no missing and data collected from entire selected sample size of the study. Findings and Research Contribution:  The primary objective of the study was to assess the influence of Islamic concept of team management and its influence on social welfare in Afghanistan. The findings of this research study contribute by having huge implications in both business and academic arena.Recommendation:  Since the analysis has found the positive relationship between the both variables such as the Islamic Concept of Team Management (Independent) and the Social Welfare (Dependent). Furthermore, the study model was found statically fit. It is highly suggested for the organization management to give more involvement to the employees while making all level decisions because the involvement of the employees in decision making will enable the organization to become more productive and market driven.
Keywords: Islam; Team Management; Organizational Welfare